FACTS AS SUBJECT MATTER OF DECLARATORY ACTION - Salma, Marija (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
Provisions of our Civil Procedure Code (CPC) relating to facts being subject matter of declaratory action deviate from comparative law. The model is unique. It deviates not only from solutions adopted in comparative law but also from traditional provisions of our previous civil procedure codes. Truth be told, the new CPC speaks of a possibility to determine facts by declaratory action when it is so provided for by the CPC itself of other regulations. The possibility to request the court to determine the authenticity of a certain document is present in all the legislation analyzed in this paper. By filing an action with such subject matter, the plaintiff, in essence, seeks final and binding assurance of the probative power of documentary evidence. A real life significance of this exception is minimal, since the court must take a position regarding the authenticity of the document if the opposing party questions it. The paper tries to identify substantive and procedural rules of law that provide for facts to be subject matter of declaratory actions. Case law analyzed in this paper does not indicate the courts being to favorable in determining facts based on a declaratory action. In fact, there have been cases, after the new CPC came into force, where the Supreme Court of Cassation dismissed a claim to determine the existence of certain facts by stating that in the case at hand the claim to determine the facts goes beyond legally permissible instances when facts may be determined by a declaratory action. We also dealt with an issue of determining the facts presented in the declaratory action. The facts are the basis for the declaratory action. Determining the facts without relying on any legal issue based on which the determination of facts is sought does not seem to be an acceptable solution.
Keywords: determination of facts; authenticity of a document; infringement of individual rights; law and legal relations